2010
DOI: 10.1016/j.cageo.2010.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional hydraulic conductivity upscaling in groundwater modeling

Abstract: The main point of this paper is to propose a non-local three-dimensional hydraulic conductivity full tensor upscaling algorithm and code. The algorithm is capable of transforming very refined cell conductivity models into coarse block conductivity models for quick and accurate solution of the groundwater flow equation. Flow rate and hydraulic head gradient are the variables used to relate the outputs from the fine scale model to the outputs from the coarse scale model. The flows and gradients computed at the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 28 publications
2
29
0
1
Order By: Relevance
“…For this purpose, the public domain code FLOWXYZ3D [ Li et al , 2010], has been developed. The details of the upscaling approach, the numerical modeling using interblock conductivity tensors, and several demonstration cases are given by Zhou et al [2010] and Li et al [2010, 2011a, 2011b]. The resulting upscaled interblock tensors produced by this approach are always of rank two, symmetric and positive definite.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, the public domain code FLOWXYZ3D [ Li et al , 2010], has been developed. The details of the upscaling approach, the numerical modeling using interblock conductivity tensors, and several demonstration cases are given by Zhou et al [2010] and Li et al [2010, 2011a, 2011b]. The resulting upscaled interblock tensors produced by this approach are always of rank two, symmetric and positive definite.…”
Section: Methodsmentioning
confidence: 99%
“…For each interblock, do the following: (1) isolate the fine‐scale conductivities within a volume made up by the interblock plus an additional “border ring” or “skin” and simulate flow, at the fine scale, within this volume. (2) As explained in many studies [e.g., Gómez‐Hernández , 1991; Sánchez‐Vila et al , 1995, 2006; Zhou et al , 2010; Li et al , 2011a], there is a need to solve more than one flow problem in order to being able of identifying all components of the interblock conductivity tensor. (3) From the solution of the flow problems, use to derive the interblock conductivity tensor.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies on upscaling have been published in past decades (e.g., Cassiraga et al, 2005;Dagan, 1994;Dagan & Lessoff, 2001;Fernàndez-Garcia et al, 2009;Fernàndez-Garcia & Gómez-Hernández, 2007;Fleckenstein & Fogg, 2008;Li et al, 2011;Renard & de Marsily, 1997;Rubin et al, 1999;Sanchez-Vila et al, 2006;Scheibe & Yabusaki, 1998;Wen & Gómez-Hernández, 1996;Zhou et al, 2010). Most of these studies have focused on upscaling the K field and have shown good preservation of the flows and heads.…”
Section: Introductionmentioning
confidence: 99%
“…If data for the small scale are available, but derivation of reliable statistical properties is impossible, numerical approaches can be used to obtain a K tensor that satisfies certain criteria, such as flow conservation or head reproduction (e.g. Zhou et al, 2010;Li et al, 2011). In the remainder of this paper, the term equivalent values will be used to indicate such calculated K tensors.…”
Section: Introductionmentioning
confidence: 99%